Purification and Characterization of Extracellular Gelatinolytic Protease from Bacillus Amyloliquefaciens H11. Issue 1 (21st January 2015) - Sai‐Ut, Samart; Benjakul, Soottawat; Sumpavapol, Punnanee; Kishimura, Hideki
Abstract Extracellular gelatinolytic enzyme from Bacillus amyloliquefaciens H11 was purified by gel filtration chromatography on Sephacryl S‐200 and ion exchange chromatography on diethylaminoethyl‐cellulose with 35% yield and 14‐fold increase in purity. Based on sodium dodecyl sulfate–polyacrylamide gel electrophoresis, the molecular weight of the purified enzyme was estimated to be 21 kDa. The optimum gelatinolytic activities of purified enzyme toward porcine gelatin were 50C and pH 8.0. The inhibitor study revealed that the purified enzyme was a metallo‐serine protease and activated by Ca2+ and Mg2+ but resistant to Triton X‐100 and methanol at a concentration of 10% (v/v). Among all gelatins, that from unicorn leatherjacket fish skin was the most preferred for hydrolysis by the purified enzyme, in comparison with porcine and tilapia counterparts. Thus, the enzyme from B. amyloliquefaciens H11 could be used as a potential protease for production of gelatin hydrolysate. Practical Applications Extracellular protease from Bacillus amyloliquefaciens H11 plays a specific catalytic role in the hydrolysis of gelatin and can be used for production of gelatin hydrolysate with bioactivities. It can also be a potential alternative for commercial protease in conversion of marine processing by‐products to generate high value‐added products.